The Analysis of Heroes’ Traits in Percy Jackson and the Olympians: The Lightning Thief - Ma'ruf, Annaz (Journal of Literature, Linguistics, & Cultural Studies, 2023)
This research analyzed the heroic portrayal of the main character, Percy Jackson, in Rick Riordan's novel "Percy Jackson and the Olympians: The Lightning Thief." The study aimed to examine the literary work and used a psychological approach to analyze Percy Jackson's psychological aspects as the central character. The theoretical framework utilized was "The Eight Traits of Heroes," developed by Scott Allison and George Goethals, encompassing traits such as caring, charismatic, inspiring, reliable, resilient, selfless, intelligent, and strong. The findings of this research indicated that Percy Jackson displayed all eight heroic traits in the novel. Additionally, the study employed "The Three Major Components of Heroes" to trace Percy Jackson's hero development throughout the story. However, it was noted that Percy also possessed a few non-heroic traits, including contemplating harm towards a bully and expressing anger towards a monster that caused his mother's death, revealing a vengeful aspect of Percy's character.